'The Impact of my Work would be Greater here than there': Implications of the International Mobility of Colombian Academics. (September 2018) - Bedenlier, Svenja
Internationalization of higher education affects academic faculty in various ways. However, the internationalization experience of faculty in Latin America, a region concerned with internationalization only quite recently, has not yet been sufficiently researched. This research gap is addressed with this qualitative interview study. Five Colombian academics relate their experiences of internationalization, with a key focus on their own international mobility and the effects this has had on their professional lives and their institutional environment. Qualitative content analysis resulted in the identification of the four wider themes of mobility as personal professional enrichment, the ability to make an impact within Colombian higher education and, on the institutional level, to engage with the concept of internationalization at home and revisiting the role of academics in advancing internationalization. These themes are discussed against the background of literature on faculty mobility and the specific situation of emerging countries.